A Low-Cost IoT-Based Environmental Monitoring and Sensor Validation Framework for Controlled- Environment Agriculture - Akmal Nizam Bin Mohammed; Mohd Rizal, Muhammad Haziq; Sulastri Sabudin; Mohd Faizal Mohideen Batcha (Journal of Advanced Mechanical Engineering Applications, 2026)
Reliable environmental monitoring is essential for controlled-environment agriculture to ensure suitable environmental conditions for crop growth and resource efficiency. This study aims to develop and validate a low-cost Internet of Things (IoT)-based environmental monitoring system for indoor hydroponic farming. The system consists of an MG811 carbon dioxide sensor, Durian Uno microcontroller, DHT22 temperature and humidity sensor, ESP8266 Wi-Fi module, and the Blynk Console dashboard for monitoring the carbon dioxide concentration, temperature, and relative humidity. The experiment was carried out at the indoor plant factory of Universiti Tun Hussein Onn Malaysia using green coral lettuce as the test crop over a 30-day growth cycle. The findings indicate that the CO₂ concentration fluctuated between 540 ppm and 1225 ppm, with an average of 789.63 ppm. The temperature and humidity were stable, ranging from 20.2°C to 21.2°C, with an average of 20.8°C, and the relative humidity ranged from 78% to 81%, with an average of 79.3%. The validation using the Kimo Instruments AMI310 handheld with a DHT22 sensor showed consistent temperature and humidity readings with small average differences of 0.28°C and 1.5%, respectively. However, the MG811 sensor showed a larger deviation in CO₂ measurements, indicating the need for further calibration or replacement with a more reliable CO₂ sensor. Overall, the proposed system demonstrates the viability of low-cost IoT-based monitoring for indoor farming and underscores the importance of sensor validation in controlled-environment agriculture.